STUDY OF FORMATION OF COCRYSTAL IBUPROFEN AND CAFFEINE - Aulia Kartini, Kathelea
Cocrystal is defined as a mixture compound of two solid components whereas in a three dimension structure. Ibuprofen has low solubility in water. The forming of cocrystal was expected to fix the solubility of ibuprofen. Ibuprofen and Caffeine are both already reported as they can form cocrystal with variant of substances, but on the other hand, there is still no evidence of both substances (ibuprofen and caffeine) could form a cocrystal with one another. In this final research, ibuprofen — caffeine cocrystal was forming by the process of neatgrinding. Ibuprofen, caffeine, mixture of ibuprofen - caffeine (1:9), (2:8), (3: 7), (4:6). (5:5), (6:4), (7:3), (8:2), (9: 1); and mixture of compound after 60 minutes of grinding, were all characterized with Fourier-Transform Infrared Spectroscopy (FTIR), Differential Thermal Analysis (DTA), Powder X-ray Diffraction (PXRD). Solubility test was examined with water and analyzed with UV-VIS Spectrophotometer in wavelength 222 nm. Higroscopisity test was examined in extreme humidity (99%) and were sampled at 3,6 and 9 hours. Water determination of the samples were obtained by Karl Fisher titration. FTIR spectra C=O streching shift in ibuprofen showed wave number shifting from 1720, 19 nm- to the lower wave number. DTA analysis proved with the forming of new endothennic curve in temperature 79,50C and 149,5 0C. Optimum ratio was estimated in (l : 1) when cocrystal had a complete peak in temperature 79,9 oc. Based on data experiment, cocrystal ibuprofen caffeine were forming since in ratio (l : 1). Cocrystal had melting temperature on 79,9 oc. Cocrystal ibuprofen caffeine has higher solubility than the ibuprofen, but on the other hand also has higher higroscopicity.